Breaking the Turnover Cycle: The Untold Power of Transformational Leadership, Workload, Communication and Satisfaction - Riana, Nia; Noerman, Teuku; Sandy Yuliaji, Eliana (FIA UB, 2026)
This study investigates the impact of transformational leadership, communication, and workload on job satisfaction and, in turn, turnover intention among loan officers in Indonesian microfinance institutions. Using SmartPLS, the research simultaneously tests both direct and mediating effects, thereby addressing gaps in prior studies that had treated these variables separately. Data were collected through purposive sampling from 159 respondents. The results indicate that transformational leadership and communication have a strong, positive, and significant impact on job satisfaction, whereas workload has a weak and non-significant effect. Regarding turnover intention, job satisfaction has a strong negative association, communication exhibits a significant negative influence, workload shows a significant positive effect, and transformational leadership has no direct significant impact. Job satisfaction partially mediates the relationship between transformational leadership and communication with turnover intention. These findings extend the application of Social Exchange Theory and the Job Demands–Resources Model to mission-driven, resource-constrained settings such as microfinance. Practically, the study suggests that strengthening leadership capability, improving communication systems, and closely monitoring workload can help organizations reduce turnover intention while sustaining performance and service quality for clients in microfinance. The results provide actionable insights for leaders and HR practitioners seeking to enhance employee retention in high-pressure microfinance environments.